PENERAPAN METODE BILHIKMAH, MAU’IZATULHASANAH, JADIL DAN LAYYINAH PADA BALAI DIKLAT KEAGAMAAN ACEH - Nurdin Nurdin (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2019)
The Qur'an and the Hadith of the Messenger of Allah (SAW) if examined carefully will be found in many ways, processes, techniques, strategies or methods that are very effective to be applied in the world of education, so that it will produce a generation of the style of Qur'an and in the style of the Messenger of Allah. But unfortunately educators and leaders today rarely involve themselves studying the verses of Al-Qur' an and the Sirah of the Messenger of Allah SAW related to various methods that he has applied in guiding his community except for only a small part. Whereas in Al-Quran there are several methods of teaching and educating that are very effective and efficient to be implemented at this time, this method has been proven to produce millions of ummah accepting Islam for the invitation of the Messenger of Allah, namely through the Bilhikmah method, Al-Mau'izah Hashanah, Al-Jadil and Al-Layyinah as described in the Qur'an letter An-Nahl verse 125. This writing aims to reveal how the learning process in the Aceh training center. The method used is descriptive with a library research approach and study of the results of field research.